Front crawl swimming coordination: a systematic review - Silva, A. F.; Seifert, L.; Fernandes, R. J.; Vilas Boas, J. P.; Figueiredo, P. (Sports Biomechanics, 2022)
Several constraints, including environmental (e.g., aquatic resistance, temperature and viscosity), organismic (e.g., anthropometry, buoyancy) and task-related (e.g., imposed swim speed or stroke rate) impact motor coordination and swimming performance. As motor coordination requires structurally organising intra- and inter-limb coupling, the purpose of this review was to update the literature concerning coordination between the upper-limbs in front crawl swimming. We focused on the effects of biomechanical, physiological, and personal (gender, skill level, and age) factors on coordination and performance. In fact, it could be highlighted that upper-limbs coordination varies with organismic, task and environmental constraints, resulting in several available motor solutions that should be adopted according to how each swimmer deals with occurring constraints. As such, there is no ideal or optimal coordination pattern that youth, learners and less-skilled swimmers should imitate.